Tourism Communication Model in Islamic Perspective - Lukmanul Hakim; Adeni Adeni (Lasigo Akademia Indonesia, 2022)
The development of technology greatly affects the changes in communication made to a tourist destination. Communication in Islamic tourism is very important in determining the ease of communication. Global Muslim Travel (GMTI) is an Islamic tourism ranking where the ACES (Access, Communication, Environment, and Services) Model covers four main areas in measuring it, one of which is 20% communication. Communication criteria include: language skills at the destination based on the language spoken by tourists from the top 30 Muslim market trips out. This research uses qualitative methods, through the collection of literature reviews and documents obtained from several other sources such as journals, magazines, the Global Muslim Trevel Index (GMTI) or news that is useful for increasing understanding of the data obtained The halal tourism communication model can be concluded that a clear communication path with relevant authorities to react in real-time to any Health emergency that can carry out there important things: destination marketing; stakeholder awareness; communication proficiency that is able to synergize in developing Islamic communication. Halal tourism communication model that is able to provide Muslim visitor guides, stakeholder education, market outreach, tour guides, and quality digital marketing in communicating.